2019
DOI: 10.1186/s13028-019-0488-7
|View full text |Cite
|
Sign up to set email alerts
|

Description of two Serratia marcescens associated mastitis outbreaks in Finnish dairy farms and a review of literature

Abstract: BackgroundInfection with Serratia spp. have been associated with mastitis outbreaks in dairy cattle herds. Environmental contamination or a point source, like a teat dip product, have often been observed to be potential sources of such outbreaks. We describe two Serratia marcescens associated mastitis outbreaks associated with a contaminated teat dip containing a tertiary alkyl amine, n,n-bis (3-aminopropyl) dodecylamine in two dairy cattle farms in Finland. S. marcescens strains isolated from milk and environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 35 publications
0
25
0
2
Order By: Relevance
“…In the Irish herds, all outbreaks had been caused by the same P. aeruginosa strain. There are some similarities with mastitis outbreaks caused by Serratia (S.) marcescens in Finnish dairy farms [ 34 ]. Epidemiological characterization of isolates from two outbreaks revealed that IMIs were associated with contaminated teat dips containing a tertiary alkyl amine, n,n-bis (3-aminopropyl) dodecyl amine.…”
Section: Discussionmentioning
confidence: 99%
“…In the Irish herds, all outbreaks had been caused by the same P. aeruginosa strain. There are some similarities with mastitis outbreaks caused by Serratia (S.) marcescens in Finnish dairy farms [ 34 ]. Epidemiological characterization of isolates from two outbreaks revealed that IMIs were associated with contaminated teat dips containing a tertiary alkyl amine, n,n-bis (3-aminopropyl) dodecyl amine.…”
Section: Discussionmentioning
confidence: 99%
“…may cause mild to severe illnesses [ 5 ]. Microorganisms may contaminate raw milk during milking, transportation, storage and processing, which pose a serious threat to the quality and safety of milk and milk products [ 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…marcescens is known to be associated with abortion [21] and mastitis outbreaks in dairy cows [22], inflammation of the digestive tract in hummingbirds [23], and necrotizing fasciitis in dogs [24]. Both P. mirabilis and S. marcescens are opportunistic pathogens in humans [25] and can be potentially transmitted through contaminated food [26].…”
Section: Advances In Biological Sciences Research Volume 14mentioning
confidence: 99%